Women’s Leadership, Sharia Law, and Society 5.0: A Review of Istibsyaroh’s Thoughts - Alfiyah, Nur; Barizi, Ahmad; Kawakip, Akhmad Nurul; Muhammad, Adamu Abubakar (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2024)
This study aims to analyze the leadership thought of Istibsyaroh, a female Islamic boarding school figure from Jombang, East Java, and its relevance in addressing leadership challenges in the Society 5.0 era. The issue of female leadership in this context remains a subject of debate, particularly concerning gender equality, the interpretation of Sharia law, and adaptation to modern technological advancements. Using a qualitative approach and a descriptive-analytical method, this study examines literature encompassing Istibsyaroh’s works, insights, and contributions, as well as the concept of female leadership in Sharia law and Society 5.0. The analysis reveals the interconnection between the qualifications of an ideal leader in the Society 5.0 era, Islamic perspectives on female leadership, and Istibsyaroh’s thoughts. The findings indicate that Istibsyaroh asserts women's right to hold political positions as long as they adhere to Islamic law, as there is no explicit evidence prohibiting female leadership in politics and governance. Through a critical review of thematic Quranic exegesis (tafsīr mawḍū‘ī) regarding scholars’ differing views on women’s political rights and leadership, it can be concluded that Islam provides space for women to engage in political leadership. Istibsyaroh’s leadership thought offers a model that emphasizes the synergy between Islamic values, gender justice, and adaptive skills in technology and global dynamics, making it relevant to addressing the complex leadership challenges of the Society 5.0 era.Abstrak: Penelitian ini bertujuan untuk menganalisis pemikiran kepemimpinan Istibsyaroh, seorang tokoh perempuan pesantren dari Jombang, Jawa Timur. serta relevansinya dalam menjawab tantangan kepemimpinan di era Society 5.0. Isu kepemimpinan perempuan dalam konteks ini masih menjadi perdebatan, terutama terkait keadilan gender, interpretasi hukum syariah, dan adaptasi terhadap perkembangan teknologi modern. Dengan pendekatan kualitatif dan metode deskriptif-analitis, penelitian ini mengkaji literatur yang mencakup karya, wawasan, dan kontribusi Istibsyaroh, serta konsep kepemimpinan perempuan dalam hukum syariah dan Society 5.0. Analisis ini mengungkap keterkaitan antara kualifikasi pemimpin ideal di era Society 5.0, perspektif Islam tentang kepemimpinan perempuan, dan pemikiran Istibsyaroh. Hasil penelitian menunjukkan bahwa Istibsyaroh menegaskan hak perempuan untuk menduduki jabatan politik selama berpegang teguh pada syariat Islam, karena tidak ada dalil eksplisit yang melarang kepemimpinan perempuan di bidang politik dan pemerintahan. Dari tinjauan kritis terhadap kajian tafsīr mawḍū‘ī (tematik) mengenai perbedaan pandangan ulama tentang hak-hak politik perempuan, dapat disimpulkan bahwa Islam memberikan ruang bagi perempuan untuk berperan dalam kepemimpinan politik. Pemikiran kepemimpinan Istibsyaroh menawarkan model yang menekankan sinergi antara nilai-nilai keislaman, keadilan gender, serta keterampilan adaptif terhadap teknologi dan dinamika global, menjadikannya relevan untuk menghadapi tantangan kepemimpinan di era Society 5.0.